Cycling and how to study it: Looking at the New Zealand case. (26th November 2020) - Latham, Alan
Abstract: Cycling has the potential to play a key role in developing environmentally and socially sustainable cities and neighbourhoods in New Zealand. Realising this potential requires understanding how different groups within New Zealand society relate to existing patterns of cycling, and how they might respond to the introduction of a range of new cycling oriented infrastructures. Commenting on articles from the special issue "New research on cycling in New Zealand, " this article argues that human geographers and other social scientists have much to offer policy makers and planners in understanding how a transition to more people oriented, sustainable, urban mobility systems might be fostered.